A method for the empirical formulation of current profile - Kim, D.K. (2019)
In this study, an advanced method was proposed for the empirical formation of current profiles. A probabilistic approach was adopted to generate a reliable empirical model which can be expressed as a function of current velocity and water depth from the obtained best-fit probability density function (PDF) with sub-parameters. It is recognised that the statistical scatter of current velocity at each normalised water depth is wide and requires a reliable method (or technique) with a refined manner to generate a simplified current profile model. From the probabilistic approach, the best-fit PDF of the current velocity distribution, including all ranges of normalised water depth is decided. In addition, sub-parameters of PDF (i.e. shape, scale, location parameters) can also be formulated as a function of normalised water depth through curve-fitting. For better understanding, three main steps which are (1) individual, (2) overall, and (3) optimised outcomes have been highlighted in order to propose the empirical formulation of current profiles. Applicability of the proposed method was verified by collecting 54 current profiles obtained from existing offshore fields, thus making it possible to generate a more accurate current profile model. Â© 2018, Â© 2018 Informa UK Limited, trading as Taylor & Francis Group.